2020
DOI: 10.1159/000509766
|View full text |Cite
|
Sign up to set email alerts
|

Vectorcardiography Findings Are Associated with Recurrent Ventricular Arrhythmias and Mortality in Patients with Heart Failure Treated with Implantable Cardioverter-Defibrillator Device

Abstract: <b><i>Background:</i></b> There is a need for refined risk stratification of sudden cardiac death and prediction of ventricular arrhythmias to correctly identify patients who are expected to benefit the most from implantable cardioverter-defibrillator (ICD) therapy. <b><i>Methods:</i></b> We conducted a registry-based retrospective observational study on patients with either ischemic (ICMP) or nonischemic dilated cardiomyopathy (NICMP) treated with ICD between 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In the present study, we outlined electrocardiographic risk factors associated with unfavorable outcomes among patients with cardiomyopathies. In adults with both dilated and hypertrophic cardiomyopathy, a greater QRS-T angle has been associated with unfavorable outcomes [ 2 , 3 , 4 , 6 ]. Similarly, in our study we observed a significantly greater QRS-T angle in patients with MACE, independently of the type of cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, we outlined electrocardiographic risk factors associated with unfavorable outcomes among patients with cardiomyopathies. In adults with both dilated and hypertrophic cardiomyopathy, a greater QRS-T angle has been associated with unfavorable outcomes [ 2 , 3 , 4 , 6 ]. Similarly, in our study we observed a significantly greater QRS-T angle in patients with MACE, independently of the type of cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…In adult patients with idiopathic dilated cardiomyopathy, a relationship between greater QRS-T angle and mortality, risk of an ICD shock or rehospitalization due to heart failure had been observed, with cut-off values ranging between >90° and 152° [ 2 , 3 , 4 ]. In our cohort, we observed a mean spatial QRS-T angle of 133° among patients with adverse outcomes, which seems to be in agreement with adult reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 lists the clinical applications of these parameters that have been validated in the literature. The spatial QRS-T angle parameter has been shown to be useful for risk stratification for cardiac events, evaluation of incident coronary disease and heart failure, and efficacy of therapy for adult hypertension and diabetes mellitus [5]. For example, in the PTB diagnostic database [3,4] ECG used in this study, the mean and standard deviation of the Spatial QRS-T angles from patients with MI and healthy controls were 87.9 • ± 46.84 • and 52.95 • ± 35.76 • , respectively, as computed using the VCG parameter extraction algorithms described in this study.…”
Section: Qrs Magnitude Predicts Ventricular Arrhythmia In Selected Co...mentioning
confidence: 99%